Does glutamine have a role in reducing infections in athletes? - Castell, L. M.; Poortmans, J. R.; Newsholme, E. A. (European Journal of Applied Physiology, 1996)
There is an increased risk of infections in athletes undertaking prolonged, strenuous exercise. There is also some evidence that cells of the immune system are less able to mount a defence against infections after such exercise. The level of plasma glutamine, an important fuel for cells of the immune system, is decreased in athletes after endurance exercise; this may be partly responsible for the apparent immunosuppression which occurs in these individuals. We monitored levels of infection in more than 200 runners and towers. The levels of infection were lowest in middle-distance runners, and highest in runners after a full or ultramarathon and in elite rowers after intensive training. In the present study, athletes participating in different types of exercise consumed two drinks, containing either glutamine (Group G) or placebo (Group P) immediately after and 2 h after exercise. They subsequently completed questionnaires (n = 151) about the incidence of infections during the 7 days following the exercise. The percentage of athletes reporting no infections was considerably higher in Group G (81%, n = 72) than in Group P (49%, n = 79, p < 0.001).